Commentary: Entropy and Skewness in the Allocation of Students to Law Schools - Ronald M. Pipkin (Washington University Law Quarterly, 1981)
I wish to comment on the obligation assumed by law schools, as the primary port of entry into the legal profession, one, to recruit selectively the intellectually best qualified aspirants to law and two, to base admission decisions upon scholastic ability and performance (or compensatory affirmative action) rather than on the basis of ascriptive status characteristics. As I will show, the former process is evincing strong signs of entropy; the latter, of continued skewness.
Keywords: Law schools; Law students; United States